Electronic Medical Records in Primary Health Care Facilities - Nurrahma, Alya Nabila; Larasati, TA; Kurniati, Intanri; Pramesona, Bayu Anggileo (Faculty of Medicine, Public Health, and Nursing, 2023)
Background: Medical records are an important element in the process of health care in health facilities. Several primary health facilities have used electronic-based medical records to improve service quality. Electronic medical records are patient medical records in electronic form that include health information of an individual that can be accessed using a computer from a network to provide effective, efficient, and integrated health services. The purpose of the study was to determine the development of the use of electronic medical records in primary healthcare facilities in Indonesia with a systematic review before the mandatory use of electronic medical records in Indonesia. Methods: This research is a systematic literature review of the use of electronic medical records in primary health facilities. Researchers searched the literature on google scholar with the keyword electronic medical records and obtained a total of 60 articles, 4 of which were inaccessible, 40 articles were not conducted in primary health facilities, and 3 articles do not contain the aspect we look for so only 13 articles were used in literature studies. Results: The implementation of medical records is carried out by all health workers who provide services from registration, triage, clinical examination, treatment, and drug prescribing. Medical record data is distributed automatically by computer. Health workers have different electronic medical record display menus according to their duties. Conclusions: The implementation of electronic medical records in primary health facilities can be carried out by medical recorders and non-medical health workers who are trained and has a different electronic medical record display menu in each service flow.